Belief in caffeine's ergogenic effect on cognitive function and endurance performance: A sham dose‐response study. (3rd May 2021) - Delang, Nathan; Irwin, Christopher; Cox, Gregory R; McCartney, Danielle; Desbrow, Ben
Abstract: This study aimed to determine if belief in caffeine's ergogenic potential influences choice reaction time (CRT) and/or running performance. Twenty‐nine healthy individuals (23.7 ± 5 years, 16 males) completed two trials (one week apart). Before the trials, participants indicated their "belief" in caffeine's ergogenic effects and previous "experience" using caffeine for performance. On arrival, participants randomly received either sham "Low (100mg; LD)" or "High (300mg; HD)" dose caffeine capsules 30‐min before commencing the CRT test, followed by a 10km run. Paired samples t ‐tests determined differences between trials for CRT latency ( Ex‐Gaussian analysis; μ‐, σ‐ and τ‐) and running performance using the entire cohort and sub‐groups exhibiting strong "beliefs"+/−"experience". Sham caffeine dose did not influence CRT (μ‐, σ‐ and τ‐respectively, LD: 400 ± 53ms vs. HD: 388 ± 41ms; LD: 35 ± 18ms vs. HD: 34 ± 17ms; LD: 50 ± 24ms vs. HD: 52 ± 19ms, all p 's > 0.05). Neither belief ( n  = 6), nor belief + experience ( n  = 4), influenced this effect. Furthermore, caffeine dose did not influence run time (LD: 49.05 ± 3.75min vs. HD: 49.06 ± 3.85min, p  = 0.979). Belief ( n  = 9) (LD: 48.93 ± 3.71min vs. HD: 48.9 ± 3.52min, p  = 0.976), and belief + experience ( n  = 6) (LD: 48.68 ± 1.87min vs. HD: 49.55 ± 1.75min, p  = 0.386) didn't influence this effect. A dose‐response to sham caffeine ingestion was not evident on cognitive or endurance performance in healthy individuals, regardless of their convictions about caffeine's ergogenicity.